Predicting hospital disposition for trauma patients: application of data-driven machine learning algorithms - Alrashidi, Nasser; Alrashidi, Musaed; Mejahed, Sara; Eltahawi, Ahmed A. (AIMS mathematics, 2024)
As a consequence of road accidents, around 1.3 million people die, and between 20 to 50 million have nonfatal injuries. Therefore, hospitals are receiving a high volume of patients in their urgent care, and a quick decision must be made regarding their treatment plans. At the admission stage, there is no information or probability about the patient's final result, regardless of if the patient will mostly die or be safely discharged from the hospital. To address this issue, this study proposed a machine learning-based framework that can predict the hospital disposition for trauma patients. The framework was developed to anticipate whether the patient would be safely discharged from the hospital or die based on a set of features collected at the admission time. In this study, the data used was collected from the King Abdulaziz Medical City (KAMC) in Riyadh, Saudi Arabia, and the performance of different machine learning algorithms was investigated, including eXtreme gradient boost (XGBoost), K-nearest neighbor, random forest, logistic regression, BRR, and support vector machine. Results show that the XGBoost algorithm demonstrated a high degree of detection and prediction accuracy for disposed-to-home patients; of the 6059 patients that were sent home, the XGBoost correctly predicted 5944 (98%) of the total. Finally, the developed framework could accurately predict hospital disposition for trauma patients with high accuracy and sensitivity levels. This system can benefit healthcare teams and insurance companies by providing them with a quick decision-making tool to determine the best treatment plan for patients.